2019
DOI: 10.1038/s41598-019-47392-1
|View full text |Cite|
|
Sign up to set email alerts
|

Performance of a glucose-reactive enzyme-based biofuel cell system for biomedical applications

Abstract: A glucose-reactive enzyme-based biofuel cell system (EBFC) was recently introduced in the scientific community for biomedical applications, such as implantable artificial organs and biosensors for drug delivery. Upon direct contact with tissues or organs, an implanted EBFC can exert effects that damage or stimulate intact tissue due to its byproducts or generated electrical cues, which have not been investigated in detail. Here, we perform a fundamental cell culture study using a glucose dehydrogenase (GDH) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…The amount of H2O2 in the cell at 0.3, 0.7 and 1 V was determined using a colorimetric assay as described in the Experimental Section. 38,40 Inset of (A) shows the H2O2 calibration curve.…”
Section: According Tomentioning
confidence: 99%
“…The amount of H2O2 in the cell at 0.3, 0.7 and 1 V was determined using a colorimetric assay as described in the Experimental Section. 38,40 Inset of (A) shows the H2O2 calibration curve.…”
Section: According Tomentioning
confidence: 99%
“…The results showed a dose-dependent increase in the distance of gene expression clusters from 127 nA/cm 2 , 248 nA/cm 2 , and 598 nA/cm 2 electrical stimulation (Supplementary Figure S2), which means the gene expression profiling significantly changed depending on the electrical current. A total of 166 up-regulated genes showing gene expression significance compared to the control in each electrical condition were used for hierarchical clustering analysis, based on log 2 Fragment per Kilobase of transcript per Million mapped reads (FPKM) values. We found that the up-regulated genes were divided into three clusters according to the highest expression level at each current (127 nA/cm 2 : red present 41,248 nA/cm 2 : blue present 68,598 nA/cm 2 : green present 57 genes).…”
Section: Transcriptomic Analysis Of Electrically Stimulated Had-mscsmentioning
confidence: 99%
“…There is broad interest in developing enzymatic biofuel cells as components within wearable sensors and bioelectronic devices to regulate cell behavior [1][2][3]. Electrical stimulation plays an important role in regulating the function of mammalian cells and tissues, including neurons, muscle, and cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Within second-generation glucose sensors, glucose is oxidized by GOx to produce gluconic acid and H 2 O 2 [6,11], and electrons generated by glucose oxidation are transferred to the electrode via an electron transfer mediator such as iron or ruthenium-a sensing concept which has been employed in commercial glucose biosensors [9,10,12]. GOx has a high temperature and pH stability along with excellent glucose substrate selectivity [13][14][15]; however, GOx uses O 2 as an external electron acceptor in the oxidation reaction so device performance is sensitive to and variable depending on the atmospheric oxygen level [16][17][18]. To overcome this challenge and improve sensing reliability, glucose dehydrogenase (GDH) does not require O 2 and is hence being used in various types of glucose sensors together with pyrroloquinoline (PQQ), nicotinamide adenine dinucleotide (NAD), and flavin adenine dinucleotide (FAD) redox cofactors [19][20][21].…”
Section: Introductionmentioning
confidence: 99%